2022
DOI: 10.1111/aec.13214
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in the diet of a native apex predator and invasive mesopredator in an alpine ecosystem

Abstract: Carnivores have key ecological roles in structuring and regulating ecosystems through their impacts on prey populations. When apex-and meso-predators co-occur in ecosystems, there is the potential for complex interspecific interactions and trophic dynamics that can affect the composition and functioning of ecological communities. Investigating the diet of sympatric carnivores can allow us to better understand their ecological roles (e.g. potential suppression of herbivores) or impacts (e.g. predation of threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…Our finding that the dingoes' dietary composition varied across seasons in the Border Ranges marks a novel addition to the literature, because studies exploring seasonal variation in dingo diets are scant (examples include: [108][109][110][111]), and none have yet been conducted in subtropical areas. However, we found no significant seasonal influence on the dingoes' diet in Richmond Range, but this is likely a consequence of smaller sample sizes in this reserve.…”
Section: Seasonal Variation In Dietmentioning
confidence: 86%
“…Our finding that the dingoes' dietary composition varied across seasons in the Border Ranges marks a novel addition to the literature, because studies exploring seasonal variation in dingo diets are scant (examples include: [108][109][110][111]), and none have yet been conducted in subtropical areas. However, we found no significant seasonal influence on the dingoes' diet in Richmond Range, but this is likely a consequence of smaller sample sizes in this reserve.…”
Section: Seasonal Variation In Dietmentioning
confidence: 86%
“…In parts of Australia where dingoes are allowed to continue to fulfill their role as apex predators, they are thought to predate heavily on deer, particular fawns (e.g., red deer Cervus elaphus in south-east Queensland and chital near Charters Towers), as well as goats (particularly kids). Thompson and colleagues [ 61 ], working in High Country Victoria, found that dingo diets typically comprised up to 44% sambar.…”
Section: Discussionmentioning
confidence: 99%